Hydrogen storage properties of V0.3Ti0.3Cr0.25Mn0.1Nb0.05 high entropy alloy. (19th July 2022) - Liu, Jingjing; Xu, Jie; Sleiman, Salma; Ravalison, Francia; Zhu, Wei; Liu, Hongfei; Cheng, Honghui; Huot, Jacques
Abstract: In this paper, we present the synthesis, first hydrogenation kinetics, thermodynamics and effect of cycling on the hydrogen storage properties of a V0.3 Ti0.3 Cr0.25 Mn0.1 Nb0.05 high entropy alloy. It was found that the V0.3 Ti0.3 Cr0.25 Mn0.1 Nb0.05 alloy crystallizes in body-centred cubic (BCC) phase with a small amount of secondary phase. The first hydrogenation is possible at room temperature without incubation time and reaches a maximum hydrogen storage capacity of 3.45 wt%. The pressure composition isotherm ( P–C–I ) at 298 K shows a reversible hydrogen desorption capacity of 1.78 wt% and a desorption plateau pressure of 80.2 kPa. The capacity loss is mainly due to the stable hydride with the desorption enthalpy of 31.1 kJ/mol and entropy of 101.8 J/K/mol. The hydrogen absorption capacity decreases with cycling due to incomplete desorption at room temperature. The hydrogen absorption kinetics increases with cycling and the rate-limiting step is diffusion-controlled for hydrogen absorption. Graphical abstract: Image 1 Highlights: V0.3 Ti0.3 Cr0.25 Mn0.1 Nb0.05 high entropy alloy with BCC phase was prepared. First hydrogenation of the alloy is without incubation time at room temperature. Maximum hydrogen storage capacity of the alloy reaches 3.45 wt%. Cycling performance of the high entropy alloy is investigated. Structure evolution after hydrogen desorption and pumping is studied.